Long-term citizen science program of the first arrival of Barn Swallows Hirundo rustica in Italy: a preliminary study on how the climate affects spring migration across the Mediterranean (Avocetta, 2025)
This study aims to present and analyze the spring migration of Barn Swallow Hirundo rustica data collected by a network of Italian birdwatchers in collaboration with a Research Institute in the framework of a citizen science project. More than 500 observations of the first sightings of Barn Swallow's arrival in Italy were collected from 2004 to 2019 throughout the country. Percentile indices were calculated for each year and four regional subdivisions of the Italian territory: Northern, Central, Southern Italy, and the main islands (Sicily and Sardinia). Our analysis showed that the first spring sightings were significantly advanced (from 1 to 1.2 days/year) during the study period. Our data also describe the progression of migration across Italy with first arrivals documented in the main island and progressing from South to North of Italy first in Sicily and Sardinia, then along the Tyrrhenian and Adriatic coasts and from there to the major mountain chains (Apennines and Alps). Analysis of climate data (February temperature) of Europe and Africa showed a recurrent pattern of years of late arrivals linked to a negative temperature anomaly over the Mediterranean and North Africa and years of early arrival with a positive temperature anomaly in the same area. First sightings were significantly correlated with December, winter and January-to-March average temperatures at a stopover site in North Africa. Our study demonstrates that analyses based on a large environmental dataset can investigate complex phenomena such as bird migration and that a high volume of data combined with statistical indices may mitigate the limitations linked to a citizen science approach.